A brief Acceptance and Commitment Therapy-based intervention among violence-prone male inmates delivered by novice therapists - Nikolett EISENBECK; Katalin SCHEITZ; Boglárka SZEKERES (Psychology, Society & Education, 2016)
Acceptance and mindfulness-oriented cognitive and behavioral therapies, such as Acceptance and Commitment Therapy (ACT) are implemented in a wide range of different populations, but are not commonly used currently in correctional facilities. Objective: This study aimed to assess an intervention based on ACT in comparison with a treatment as usual condition (TAU) among inmates. Method: We compared 10 group sessions of ACT (n=9) with TAU (n=8) among male prisoners charged with violent crimes, administered by novice ACT therapists. Results: At postintervention, ACT was more effective in enhancing values-consistent behaviors than TAU as measured by the Valued Living Questionnaire. Depression, anxiety and psychological flexibility did not change after any of the treatments. These results were maintained at three-month follow-up. Conclusions: A brief ACT intervention delivered by inexperienced ACT therapists can be effective in increasing values-behavior consistency among male inmates. ACT may be a viable and cost-effective intervention alternative in penitentiary contexts.